2007
DOI: 10.1007/s10856-007-0143-0
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus adhesion to standard micro-rough and electropolished implant materials

Abstract: Implant-associated infections can cause serious complications including osteomyelitis and soft tissue damage, and are a great problem due to the emergence of antibiotic resistant bacteria such as methicillin-resistant Staphylococcus aureus (MRSA). In some cases, antibiotic-loaded beads which release the antibiotic locally have been used, however such systems may lead to the development of antibiotic-resistant bacteria, as seen with gentamicin-loaded beads. Hence modifying the actual metal implant surface to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 33 publications
6
68
0
1
Order By: Relevance
“…Given the very low rate of BF, SSS seemed the best biomaterial in vitro. P. aeruginosa biofilms attached strong to TI in our study, according to Staphylococcus biofilms, as described by Harris et al [9]. Furthermore, in our study ES I3 resulted in a greater reduction of the biofilm than ES I1, although the protein concentration is equal in both ES.…”
Section: Discussionsupporting
confidence: 81%
“…Given the very low rate of BF, SSS seemed the best biomaterial in vitro. P. aeruginosa biofilms attached strong to TI in our study, according to Staphylococcus biofilms, as described by Harris et al [9]. Furthermore, in our study ES I3 resulted in a greater reduction of the biofilm than ES I1, although the protein concentration is equal in both ES.…”
Section: Discussionsupporting
confidence: 81%
“…microrough, polished), and the type of plate (e.g. locking compression plate (LCP), dynamic compression plate (DCP)) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation is a multi-step process (Gristina, 1987;An and Friedman, 1998) and extensive research on medical devices and their propensity for biofilm formation by staphylococci has been performed during the last years (Harris and Richards, 2006). Several factors, such as surface hydrophobicity (Jakubowski et al, 2008), surface charge (Oga et al, 1988), surface roughness (Harris et al, 2007) and surface chemistry (Abraham and Jefferson, 2010;MacKintosh et al, 2006;Patel et al, 2003;Patel et al, 2007) have been shown to influence biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as surface hydrophobicity (Jakubowski et al, 2008), surface charge (Oga et al, 1988), surface roughness (Harris et al, 2007) and surface chemistry (Abraham and Jefferson, 2010;MacKintosh et al, 2006;Patel et al, 2003;Patel et al, 2007) have been shown to influence biofilm formation. But the effect of these findings on bone grafts in clinical practice is unclear and the use of fresh autologous bone grafts is still regarded the standard procedure to fill bone defects (Delloye et al, 2007;De Long et al, 2007;Ketonis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%